Penerapan QrCode dan Digital Signature Menggunakan Algoritma SHA Untuk Lembar Disposisi Elektronik - Ifriandi Labolo; Bahtiar Senung (STMIK Budi Darma, 2022)
Abstract is a brief summary of the paper to help readers quickly determine the main research problem, solutions to solving problems Utilization of information technology in the field of government administration can improve service quality and the performance of government officials to be more leverage. The distribution process of disposition letters to government agencies often encounters many obstacles, including the absence of authorized officials in the disposition process being the reason an agenda cannot be processed at the right time. Another thing is also related to the paperless reduction campaign in an agency, both public and private, which is being carried out to reduce paper usage. The change from manual to automatic, or from manual paper to electronic documents is natural to do, but the legality process of a document electronics will be a problem if it is not equipped with a digital signature and qrcode. This study takes the idea of utilizing QRCode and Digital signatures with the SHA algorithm which is applied to smartphones with the Android operating system to simplify the process of distributing electronic disposition sheets so as to reduce the use of paper in the government environment. The results of this research are able to create Digital signatures and QRCodes for electronic documents on a system to be more reliable. The signature on the document is replaced with a QRCode which is generated using the SHA Algorithm as a unique marker of a document. This QRCode also helps when related parties validate the validity of digital documents